Efficacy of phenobarbital in treating elderly epilepsy patients in rural northeast China: A community-based intervention trial. (July 2021) - Li, Nan; Li, Jing; Zhao, Danyang; Lin, Weihong
Highlights: The elderly epilepsy patients had a good response to phenobarbital monotherapy. Early-onset epilepsy patients complained of more serious adverse events but more late-onset epilepsy patients were prone to withdraw due to side effects. Non-adherence was the commonest cause of drug withdrawal, and it reflects the limited education regarding the impact of seizures and the differences in priorities of rural communities. Patients with early-onset epilepsy survive longer than patients with late-onset epilepsy. Abstract: Object: To provide information on the characteristics of elderly epilepsy patients in rural Northeast China. Method: Consecutive patients (aged >60) who were diagnosed with convulsive epilepsy in seven counties in Jilin Province, Northeast China, between January 2010 and December 2019 were included in the program and were divided into the EOE (early-onset epilepsy) group and the LOE (late-onset epilepsy) group. The patients were followed up once a month, and demographics and clinical data were recorded. Result: There were 471 patients enrolled in this study, with 329 patients classified into the EOE group and 142 patients recruited into the LOE group. At baseline, the EOE group was younger than the LOE group (t=-9.007, p < 0.001). The most common etiologies for the EOE and LOE groups were post-trauma (4.0%, n =13) and stroke (9.2%, n =13). Elderly epilepsy patients had a good response to PB monotherapy, and no significant difference was found between the two groups ( p > 0.05). EOE patients complained of more serious adverse events ( p < 0.05), and drowsiness (52%) and ataxia (28%) were the most common adverse events reported by the EOE and LOE groups, respectively; however, more LOE patients were prone to withdrawal due to side effects ( p  = 0.036). A total of 63 patients withdrew from the study, and nonadherence was the commonest cause for withdrawal (56% in EOE and 50% in LOE). In the entire follow-up period, 112 patients (63 in the EOE group and 49 in the LOE group) died; the most common causes of death were stroke (n=44, 39%) and heart disease (n=36, 32%). The LOE group had a shorter survival time than the EOE group (χ 2 =42.216, p < 0.001). The LOE group (HR=3.47, 95% CI: 2.36-5.09) and higher seizure frequency (HR=1.72, 95% CI: 1.17-2.52) were the risk factors for death. Conclusion: Elderly epilepsy patients had a good response to PB monotherapy. EOE patients complained of more serious adverse events, but more LOE patients were prone to withdrawal due to side effects. Nonadherence was the commonest cause of drug withdrawal, and it reflects the limited education regarding the impact of seizures and the differences in priorities of rural communities. EOE patients survive longer than LOE patients.